Migration and Redistribution: Why the Federal Governance Structure of the Economic Union Matters - Assaf Razin; Efraim Sadka (Center for Economic Studies and ifo Institute (CESifo), 2016)
We argue that the degree of coordination among the member states potentially contribute a great deal to our understanding of observed policy differences between the EU and the US as economic unions: the generosity of the welfare state and the skill composition of migration.
Keywords: 330